Assessing and Predicting the Distribution of Riparian Invasive Plants in Continental Portugal - Pabst, Rebecca; Dias, Filipe S.; Borda-de-Água, Luís; Rodríguez-González, Patricia María; Capinha, César (Frontiers in Ecology and Evolution, 2022)
The number of alien plant species is growing steadily across all world regions. These numbers tend to be exceptionally high in riparian ecosystems, often with substantial negative consequences for native species communities and ecosystem services provision. Here, we map the richness of invasive alien plant species in riparian ecosystems of continental Portugal, assess the relative importance of human and natural factors in shaping the uncovered patterns, and predict richness values along watercourses and at the municipal level for the whole study area. We found a higher richness of invasive alien plants in low altitudes and in downstream areas where human concentration is high. As time progresses, on-going and increasing levels of socio-economic activity and globalization of plant trade will conceivably lead to a higher number of alien species becoming established. National and sub-national measures aim-ing to prevent and manage biological invasions in riparian ecosystems require coordinated efforts in-volving both local entities and those with responsibilities in the management of upstream catchment areas. These efforts must also be targeted to achieve future biodiversity protection goals as part of the EU Biodiversity Strategy for 2030.